KINERJA KARYAWAN SWALAYAN MEKAR KOTA KEDIRI DIPENGARUHI OLEH DISIPLIN DAN KOMPENSASI KERJA - Iing Sri Hardiningrum (Faculty of Social and Political Science, 2018)
The main factor of employee assesment performance is very important to plan and evaluate of company overall. This study aims to analyze several variables that influence the performace employees of “Mekar” Departement store Kediri. The variables that referred to is dicipline and compenzation employees. Research methods that were used of these tests are quantitive within 73 people, “Mekar” depertment store Kediri as sampels. Statistic analysis technique that is used is using the tools of multiple regression with SPSS software.Based on calculation on obtained that the regression coefficient of 59.1% for variable compensation and 40.1% for dicipline variable. The results of this proves that employees will be had more a good performance , if all employees appreciated be compensated according to his job. The remembrance of compensation is the variable who is influential dominant on the performance of employees , so bloom supermarkets in the kabupaten kediri , it is expected that besides prioritizing financial compensation also non financial compensation to employees who performed well given a position promotion or an award as can also be done by providing education and training so that the employees more aggressive in in working.